The effect of acoustically enriched environment on structure and function of the developing auditory system - Bureš, Zbyněk; Svobodová Burianová, Jana; Pysanenko, Kateryna; Syka, Josef (Hearing research, 2024)
It has long been known that environmental conditions, particularly during development, affect morphological and functional properties of the brain including sensory systems; manipulating the environment thus represents a viable way to explore experience-dependent plasticity of the brain as well as of sensory systems. In this review, we summarize our experience with the effects of acoustically enriched environment (AEE) consisting of spectrally and temporally modulated complex sounds applied during first weeks of the postnatal development in rats and compare it with the related knowledge from the literature. Compared to controls, rats exposed to AEE showed in neurons of several parts of the auditory system differences in the dendritic length and in number of spines and spine density. The AEE exposure permanently influenced neuronal representation of the sound frequency and intensity resulting in lower excitatory thresholds, increased frequency selectivity and steeper rate-intensity functions. These changes were present both in the neurons of the inferior colliculus and the auditory cortex (AC). In addition, the AEE changed the responsiveness of AC neurons to frequency modulated, and also to a lesser extent, amplitude-modulated stimuli. Rearing rat pups in AEE leads to an increased reliability of acoustical responses of AC neurons, affecting both the rate and the temporal codes. At the level of individual spikes, the discharge patterns of individual neurons show a higher degree of similarity across stimulus repetitions. Behaviorally, rearing pups in AEE resulted in an improvement in the frequency resolution and gap detection ability under conditions with a worsened stimulus clarity. Altogether, the results of experiments show that the exposure to AEE during the critical developmental period influences the frequency and temporal processing in the auditory system, and these changes persist until adulthood. The results may serve for interpretation of the effects of the application of enriched acoustical environment in human neonatal medicine, especially in the case of care for preterm born children.
Keywords: Neurons; Rats; Auditory system; Animals, Newborn; neuroplasticita; Auditory Cortex; Auditory Pathways; Neuronal Plasticity; Critical period; Plasticity; sluchová percepce; Inferior Colliculi; novorozená zvířata; krysa rodu Rattus; věkové faktory; sluchová dráha; zvířata; Acoustic Stimulation; colliculus inferior; Humans; Acoustically enriched environment; neurony; Environment; Development; akustika; Acoustics; Age Factors; Auditory Perception; akustická stimulace; životní prostředí; lidé; sluchové korové centrum; Animals